2010
DOI: 10.1111/j.1365-2443.2010.01466.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitro-fatty acids and cyclopentenone prostaglandins share strategies to activate the Keap1-Nrf2 system: a study using green fluorescent protein transgenic zebrafish

Abstract: Nitro-fatty acids are electrophilic fatty acids produced in vivo from nitrogen peroxide that have many physiological activities. We recently demonstrated that nitro-fatty acids activate the Keap1-Nrf2 system, which protects cells from damage owing to electrophilic or oxidative stresses via transactivating an array of cytoprotective genes, although the molecular mechanism how they activate Nrf2 is unclear. A number of chemical compounds with different structures have been reported to activate the Keap1-Nrf2 sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 39 publications
3
61
0
Order By: Relevance
“…Although several in vitro experiments have shown that Cys151, Cys273, and Cys288 are highly reactive to many electrophiles (10)(11)(12)(13)(14)(15)(16)(17), evaluation of the sensor function of Cys273 and Cys288 has not been technically feasible, since replacements of Cys273 and Cys288 with serine or alanine render Keap1 unable to ubiquitinate and repress Nrf2 (18,19,21). To overcome this problem, we attempted a systemic analysis by introducing amino acid substitutions into Cys273 and Cys288 sites of human KEAP1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although several in vitro experiments have shown that Cys151, Cys273, and Cys288 are highly reactive to many electrophiles (10)(11)(12)(13)(14)(15)(16)(17), evaluation of the sensor function of Cys273 and Cys288 has not been technically feasible, since replacements of Cys273 and Cys288 with serine or alanine render Keap1 unable to ubiquitinate and repress Nrf2 (18,19,21). To overcome this problem, we attempted a systemic analysis by introducing amino acid substitutions into Cys273 and Cys288 sites of human KEAP1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6D) and 4-HNE (Fig. 6E), both of which were reported to exploit Cys273 and Cys288 to modify Keap1 activity (15,16,34), resulted in the accumulation of Nrf2 in both wild-type and Keap1 C288E/C288E macrophages. To our surprise, PGA 2 induced Nrf2 accumulation in Keap1 C288E/C288E macrophages (Fig.…”
Section: Knock-in (Keap1mentioning
confidence: 99%
See 2 more Smart Citations
“…Urinary Kelch-like ECH-associated protein 1 (Keap1) regulator of nuclear factor (erythroid-derived-2)-like 2 (Nrf2), heat shock factor-1 (HSF-1), peroxisome proliferator-activated receptor-␥ (PPAR ␥ ), and histone deacetylases (HDAC) ( 7 ). These transcriptional regulatory proteins contribute to the control of the expression of hundreds of genes that include cytokines, antioxidant enzymes, heat shock response proteins, and enzymes of intermediary metabolism ( 4,5,(8)(9)(10)(11)(12)(13)(14).…”
Section: Lipid Extraction From Urinementioning
confidence: 99%